Implementasi Undang-Undang Ketenagakerjaan Dalam Perjanjian Kerja Antara Perusahaan Dan Tenaga Kerja Di PTPN IV Bandar Pasir Mandoge - Purba, Bonaraja; Hasyim, Hasyim; Lubis, Andi Syahputra; Margaretha, Dewi; Hidayat, Taufik; Humairah, Zaskya (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Employment Agreement is an Agreement or agreement that is established between a union or trade unions that have been registered with the labor department with employers or associations of entrepreneurs who are legal entities, which in general or merely contain work conditions that must be considered in the employment agreement. The formulation of the problem in this study is how the implementation of the employment agreement in a limited company is reviewed from the labor legislation and whether the work agreement made by a limited liability company (PT) with the worker has fulfilled the elements of the employment agreement according to Law No. 13 of 2003 concerning Employment. The research method uses literature study and field research. The results of this study conclude that currently there are still several companies that still include the arguments of work agreements between companies and employees that are contrary to Law Number 13 of 2003 concerning Manpower, namely if one company does not pay employee leave that has not been taken or fall, then the employee has the right to get compensation money in accordance with the provisions of the law.